Interpersonal teamwork among ethnic groups toward economic development in transmigration areas (Research, Society and Development, 2020)
This study purposed to reveal some interpersonal teamwork form as well as remarkable social norms for mutual interest in economic development among members of ethnic groups in transmigration areas. The method used in this research is qualitative. The finding indicated that the most dominant social field influencing social teamwork interaction was economic life. The form of the teamwork could be seen in the paddy field, in the processing of rice fields and rice cultivation in the marketing of agricultural products. This cooperation among ethnic groups was based on the values and norms adopted by each ethnic group.